Alternative Settlement of Medical Malpractice Cases in The Perspective of Legal Sociology - Adil Akhyar (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
Medical malpractice always gets the spotlight or complaints and catches the law enforcement officials as a mistake made by doctors, midwives, nurses, pharmacists or hospitals. In fact, it is not uncommon for cases like this to be exposed in the mass media and other social media, as if the suspect suspected of committing malpractice had indeed committed the act (Media as a Pre-Court). In addition to requiring proof and the opinion of experts in their field, a health practitioner is a noble occupation, so good name is also valuable in carrying out their activities as health practitioners. Cases of suspected medical malpractice are rarely examined in terms of causality (cause and effect), whereas reviewing other actions as a cause and effect of the alleged malpractice is important, which is why it is necessary to use Restorative Justice before taking action, especially in cases of medical malpractice. This paper describes the existence of the Restorative System in the Indonesian judicial system as a concept that is very relevant if used to resolve cases related to health practitioners and good name in carrying out their profession. This paper is conceptual with descriptive analysis method. It can be concluded that the Restorative system in the settlement of Malpractice cases is a way out of the problems and trauma faced by health practitioners as a win-win solution in the face of claims or demands against them.